Kinetics of Strecker aldehyde formation during thermal and high pressure high temperature processing of carrot puree. (February 2017) - Kebede, Biniam; Grauwet, Tara; Andargie, Tewodros; Sempiri, Geoffery; Palmers, Stijn; Hendrickx, Marc; Van Loey, Ann
Abstract: Strecker aldehydes have been negatively associated to flavor of heat sterilized plant-based foods. The present study demonstrated the importance of processing conditions (temperature, pressure and time) as a strong means for the control of Strecker aldehyde formation in vegetables purees. A kinetic study was set up (at isothermal and isothermal-isobaric conditions) to quantify the effects of single process parameters on the changes of 3-methylbutanal (3-MB) in carrot puree as a case study. The increase in 3-MB concentrations was best described by an empirical, logistic model. During the isothermal treatment at atmospheric pressure, the maximum reaction rate constant of 3-MB formation was increased as a function of processing temperature. However, the formation rate was clearly slower at high pressure (600 MPa) compared to the process at 0.1 MPa. Hence, the reduced formation of Strecker aldehydes under high pressure could open a new possibility for process control and optimization of the formation of these compounds. Industrial relevance: High pressure high temperature (HPHT) processing is a relatively young technology and its effect on important quality-related chemical reactions is not as well understood as is the case for conventional thermal processing. The present work investigates the impact of processing conditions (e.g. pressure, temperature) on Strecker aldehydes formation, volatiles that have been negatively associated to flavor of heat sterilized plant-based foods. Based on the kinetic study, the formation rate of the Strecker aldehyde (3-methylbutanal) was clearly slower at high pressure (600 MPa) compared to the process at 0.1 MPa in carrot puree. Considering the fact that these compounds are often linked to off-flavor development, their reduced formation under high pressure could open a new possibility for process control and optimization. Highlights: Strecker aldehydes are negatively associated to flavor of heat sterilized foods. Processing at 600 MPa slows Strecker aldehyde formation rate than at 0.1 MPa. At 0.1 MPa, Strecker aldehyde formation rate increases as a function of temperature.